2017
DOI: 10.2298/ntrp1703288b
|View full text |Cite
|
Sign up to set email alerts
|

Radiation shielding and gamma ray attenuation properties of some polymers

Abstract: In the pres ent work we in ves ti gated the gamma ra di a tion pa ram e ters as mass at ten u a tion coef fi cients m/r, the to tal atomic scat ter ing cross-sec tions s t , the elec tronic scat ter ing cross-sections s e , the ef fec tive atomic num bers Z eff , and the ef fec tive elec tron den si ties N eff for some poly mers such as polyoxymethylene (CH 2 O), poly acrylonitrile (C 3 H 3 N), nat u ral rub ber (C 5 H 8), poly ethyl acrylate (C 5 H 8 O 2), polyphenyl methacrylate (C 10 H 10 O 2), and poly eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Besides, polymers proved their performance and applicability in nuclear medicine as radiation shielding against Technetium-99m, where complexed grafted low-density polyethylene films revealed that the protection efficiency of complexed grafted films was higher than in grafted and virgin films (Awadallah-F and Antar 2014 ). Also, most frequently used polymers such as POM—polyoxymethylene, PAN—polyacrylonitrile, NR—natural rubber, PEA—polymethyl acrylate, PPM—poly-phenyl-methacrylate, PET—polyethylene terephthalate (Bhosale et al 2017 ) and polyamide (nylon 6) (PA-6), polyacrylonitrile (PAN), polyvinylidene chloride (PVDC), polyaniline (PANI), polyethylene terephthalate (PET), polyphenylene sulfide (PPS), polypyrrole (PPy), and polytetrafluoroethylene (PTFE) (Kaçal et al 2019 ) were studied in terms of their gamma radiation attenuation. Polyacrylonitrile, natural rubber, and polyvinylidene chloride have the highest attenuation coefficient values.…”
Section: Polymers Used In Radiological Protectionmentioning
confidence: 99%
“…Besides, polymers proved their performance and applicability in nuclear medicine as radiation shielding against Technetium-99m, where complexed grafted low-density polyethylene films revealed that the protection efficiency of complexed grafted films was higher than in grafted and virgin films (Awadallah-F and Antar 2014 ). Also, most frequently used polymers such as POM—polyoxymethylene, PAN—polyacrylonitrile, NR—natural rubber, PEA—polymethyl acrylate, PPM—poly-phenyl-methacrylate, PET—polyethylene terephthalate (Bhosale et al 2017 ) and polyamide (nylon 6) (PA-6), polyacrylonitrile (PAN), polyvinylidene chloride (PVDC), polyaniline (PANI), polyethylene terephthalate (PET), polyphenylene sulfide (PPS), polypyrrole (PPy), and polytetrafluoroethylene (PTFE) (Kaçal et al 2019 ) were studied in terms of their gamma radiation attenuation. Polyacrylonitrile, natural rubber, and polyvinylidene chloride have the highest attenuation coefficient values.…”
Section: Polymers Used In Radiological Protectionmentioning
confidence: 99%
“…So sample S6 has superior γ-ray shielding capacity than the compared commercial glasses owing to its′ larger 'µ' than them. Earlier, SS403, CN, CS516, IL600, and MN400 alloys [57], C5H8, C3H3N, C5H8O2, C10H8O4, CH2O, and C10H10O2 polymers [58], and concretes, such as OC, BMC, HSC, IC, ILC, SMC, and SSC [59] were also reported for nuclear radiation shielding purpose by other researchers. For high Z elements (e.g., Bi) containing compounds, generally, at <0.5 MeV photon energies, the PEA (all photon energy fully passing on to a bound electron) is so common, and the CS phenomenon prevails at relatively moderate and greater γ-ray energies (~500 KeV-1.5 MeV).…”
Section: γ-Ray Shielding Featuresmentioning
confidence: 87%
“…Ef fec tive atomic num ber, Z eff , is im por tant for the de ter mi na tion of a sub sti tute ma te rial for an el e -ment as so ci ated with the re quired en ergy. The ef fective atomic num ber [17,18] is equal to the ra tio of the atomic and elec tronic cross-sec tions…”
Section: Ef Fec Tive Atomic Num Bermentioning
confidence: 99%